2013
DOI: 10.3324/haematol.2013.090209
|View full text |Cite
|
Sign up to set email alerts
|

High pre-transplant serum nitrate levels predict risk of acute steroid-refractory graft-versus-host disease in the absence of statin therapy

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nThe purpose of the present retrospective study was to investigate whether the predictive value of pre-transplant levels of parameters representing endothelial cell function, such as angiopoietin-2, could be further refined by measuring pre-transplant nitrate levels, and to analyze whether negative influences on clinical outcome could be attenuated by (potentially endothelium-protective) concomitant statin administration. Methods Eligibility of patientsPatients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Because pretransplantation ANG2 and serum nitrates have been shown to predict refractoriness of acute GVHD episodes, 6 we also tested if these serum markers correlated with high-risk THBD genotypes. As summarized in Table 1, high-and low-risk THBD genotypes had similar pretransplantation serum levels of ANG2 and nitrates.…”
Section: Lack Of Correlation Of Thbd Snps With Pretransplantation Sermentioning
confidence: 99%
See 2 more Smart Citations
“…Because pretransplantation ANG2 and serum nitrates have been shown to predict refractoriness of acute GVHD episodes, 6 we also tested if these serum markers correlated with high-risk THBD genotypes. As summarized in Table 1, high-and low-risk THBD genotypes had similar pretransplantation serum levels of ANG2 and nitrates.…”
Section: Lack Of Correlation Of Thbd Snps With Pretransplantation Sermentioning
confidence: 99%
“…Serum markers were measured before conditioning therapy: Sera for measuring nitrates, soluble thrombomodulin, and ANG2 were available for 240 patients. 6 The validation cohort consisted of patients who underwent allografting at the Charité, Campus Benjamin Franklin (Berlin, Germany), between August 1995 and December 2011 and had DNA available for testing for the three significant SNPs (rs1962, rs1042579, and rs1042580). Written informed consent according to the Declaration of Helsinki was obtained for all eligible patients, and our local ethics committee approved the sample and data collection.…”
Section: Patient Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested that vascular endothelial vulnerability and endothelial dysfunction are involved in the pathogenesis of GVHD. [11][12][13] Elevated pretransplant serum levels of angiopoietin-2, a hormone mediating vascular vulnerability, and nitrate are noted in steroidrefractory GVHD patients. 11,12 A marker of endothelial damage including soluble TM is elevated in patients with steroid-refractory GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Elevated pretransplant serum levels of angiopoietin-2, a hormone mediating vascular vulnerability, and nitrate are noted in steroidrefractory GVHD patients. 11,12 A marker of endothelial damage including soluble TM is elevated in patients with steroid-refractory GVHD. 13 These observations encouraged us to hypothesize that the prophylactic use of rTM with cytoprotective as well as antiinflammatory activity would decrease the incidence of GVHD in transplant patients.…”
Section: Introductionmentioning
confidence: 99%